Unilateral esophageal lung with dextroposition of the heart - Abdulaziz Khaled Aldosari; Shahad Bakr Alwazzan; Abdullah Mohammad Alotaibi (Elsevier, 2022)
Esophageal lung is a rare type of congenital bronchopulmonary foregut malformation (CBPFM) that is difficult to diagnose. The authors report a case of esophageal lung that presented postnatally with respiratory distress and associated heart and skeletal anomalies. After proper investigations and evaluations, the patient was managed surgically with right total pneumonectomy.